(untitled) (Research, Society and Development, 2024)
The sacred forests of the Western Highlands Cameroon are, like other forests, a reserve of plants and genes, both known and unknown. They are privileged places for communication with ancestors. They provide significant environmental and socio-economic benefits; despite the pressure they are increasingly coming under. The aim of this study is to categorise the different uses of the sacred forests of Bafou, Baleveng and Bamendou, and then to assess the carbon stock of the woody plants in these forests. A survey form was used to record the various benefits derived by local people from the sacred forests. Individuals were counted in 30 m x 100 m plots. All individuals with a diameter ≥5 cm at 1.30 m above ground were considered. Carbon sequestered by forests was estimated using the non-destructive method. The study shows that the traditional laws protecting these forests are increasingly being violated by local people. These forests are cultural properties for the village and provide the local population with a variety of products. The most frequently cited uses are firewood, food products, medicinal plants and sacrifices. A total of 54 species, 47 genera and 29 families have been identified. Of these species, around 40.35% are used in one way or another by local people. The values of carbon sequestered by these forests vary from one forest to another and according to the type of equation chosen. The Bamendou sacred forest recorded the highest value, 443.9 t C /ha and 287.79 t C /ha respectively, using the equations of Djomo et al. (2010) and Fayolle (2013). This work presents the benefits of sacred forests for local populations. Management strategies for these forests should be strengthened by the State to ensure more sustainable conservation of this rich heritage.